Non-spherical polymersomes: formation and characterization - Wong, Chin Ken; Stenzel, Martina H; Thordarson, Pall (Chemical Society reviews, 2019)
Polymersomes are self-assembled hollow membrane sacs that are not only able to encapsulate hydrophobic and/or hydrophilic molecules, but also possess exceptional chemical and physical stability, structural versatility, and surface modifiability. For the above reasons, polymersomes have in recent years emerged as a powerful tool for a wide range of applications in the fields of biomimicry and drug delivery. The full potential of polymersomes, however, has yet to be harnessed due to a lack of appreciation of existing shape control methods. This very much contrasts the field of inorganic nanoparticle synthesis where non-spherical hollow metal nanoparticles are routinely prepared and used. Here, we summarize recent efforts over the past decade to study the morphological transformation of conventionally spherical polymersomes into non-spherical polymersomes.